2017
DOI: 10.3892/etm.2017.4082
|View full text |Cite
|
Sign up to set email alerts
|

Role of neural barriers in the pathogenesis and outcome of Streptococcus pneumoniae meningitis

Abstract: Bacterial meningitis is an inflammatory disease of the meninges of the central nervous system (CNS). Streptococcus pneumoniae (S. pneumoniae), Neisseria meningitidis, and Haemophilus influenzae are the major bacterial pathogens causing meningitis with S. pneumoniae being responsible for two thirds of meningitis cases in the developed world. To reach the CNS following nasopharyngeal colonization and bacteraemia, the bacteria traverse from the circulation across the blood brain barrier (BBB) and choroid plexus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 181 publications
0
10
0
Order By: Relevance
“…We detected both expansion of the anti-infective components of CSF (immunoglobulins and complement) and high levels of expression of neutrophil-associated proteins including S100A8/ 9, cathepsin, neutrophil defensin, and matrix-metalloproteinases 9 (MMP9) that infection models have suggested are detrimental to the host (Tuomanen et al, 1989;Roine et al, 2014;Mohanty et al, 2019). Severe BBB breakdown has previously been assumed to be a pre-morbid event in PM (Barichello et al, 2011;Prager et al, 2017), and quantifying BBB breakdown in patients is complex (Helms et al, 2016;Prager et al, 2017;Natarajan et al, 2017). In this dataset, which is controlled for protein abundance, the presence of both brain-derived proteins (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…We detected both expansion of the anti-infective components of CSF (immunoglobulins and complement) and high levels of expression of neutrophil-associated proteins including S100A8/ 9, cathepsin, neutrophil defensin, and matrix-metalloproteinases 9 (MMP9) that infection models have suggested are detrimental to the host (Tuomanen et al, 1989;Roine et al, 2014;Mohanty et al, 2019). Severe BBB breakdown has previously been assumed to be a pre-morbid event in PM (Barichello et al, 2011;Prager et al, 2017), and quantifying BBB breakdown in patients is complex (Helms et al, 2016;Prager et al, 2017;Natarajan et al, 2017). In this dataset, which is controlled for protein abundance, the presence of both brain-derived proteins (e.g.…”
Section: Discussionmentioning
confidence: 92%
“…Traditional treatment of S. pneumoniae infection by antibiotic only reduced bacterial load but not be able to rescue neuronal injury (Kadurugamuwa et al, 2005). BBB opening controlled by TNF is necessary for the development of meningitis (Tsao et al, 2002; Prager et al, 2017). Previous studies showed that an inhibitor of TNF-α converting enzyme and MMP efficiently decreased neuronal injury and improved survival without inhibiting bacterial growth (Meli et al, 2004; Echchannaoui et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…NSC 34 38 and U251 39 cell-lines were used due to their neural origin. S. pneumoniae , Neisseria meningitidis and Haemophilus influenzae are the major bacterial pathogens causing meningitis, with S. pneumoniae being responsible for two thirds of meningitis cases in the developed world 54 , 55 . NSC 34 is a mouse neuroblastoma-spinal cord hybrid immortalized cell-line 38 , which has been used to study differentiation and characteristics of motor neuron 56 , 57 .…”
Section: Discussionmentioning
confidence: 99%